Osporavanje tradicije u poemi 'Pakao" Gea Mileva - Bijelić, Marijana (Array, 2014)
Inferno (Ад), a poem by Geo Milev, is interpreted from the perspective of its dismissive attitude toward literature and cultural tradition, which is typical of avant-garde literature. The first part of the poem (I-III) is dominated by the polemic relation to the traditional and confessional concepts of hell as well as to the whole literary tradition symbolized by Dante and his poem Inferno. In its second part (IV) Milev’s poem Inferno provokes traditional views of the classical ideal of the sublime and beautiful as it puts the poor people’s empty stomach or the great hunger in the center of the infernal urban space. The cited motifs mark the negativity in the centre of the social order and their metaphorical transformation into a military drum imposes the imperative of a total social transformation, that is of a revolution.